The effectiveness of cognitive therapy based on mindfulness on emotion regulation and type D personality type symptoms in cardiac patients with ICD - Haddad, Sepideh; Khalatbari, Javad; Zarbakhsh Bahri, Mohammadreza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Today, heart diseases are one of the main causes of death in most countries of the world. The present study was conducted with the aim of determining the effectiveness of mindfulness-based cognitive therapy on emotion regulation and personality type D syndromes in cardiac patients with ICD. Methods: The research method was a quasi-experiment with a pre-test-post-test design with a control group and a three-month follow-up. The statistical population of this study were cardiac patients who had referred to Rasht hospitals from the beginning of 2021 to the end of September 1400 for the purpose of ICD implantation. Using simple random sampling, a sample of 30 people was selected. The data collection tool was the emotion regulation scale (Gross and John, 2003) and the type D personality type scale (Denault, 1998). The experimental and control groups were pre-tested using research tools. Then cognitive therapy based on mindfulness was implemented during eight sessions for the experimental group, but the control group did not receive any intervention. At the end of the intervention, the experimental and control groups were post-tested using research tools. Three months later, a follow-up test was performed on both experimental and control groups. Results: The results of multivariate covariance analysis showed that cognitive therapy based on mindfulness on emotion regulation (F=28.94, P<0.05) and type D personality type symptoms (F=4.66, P<0.05) P) is effective in cardiac patients with ICD. These results were sustained in the three-month follow-up. Conclusion: Considering the economic, social and psychological burden that heart disease imposes on individuals, families and society, the results of this research can be promising for heart patients, health and mental health professionals.